The role of Green Human Resources Management as a Mediator of Green Transfortamtional Leadership and Green Servant Leadership Relations towards Green Creativity in Hotel and Tourism Services - Ahmad Mauledy (Dinasti Publisher, 2023)
Abstract: This study aims to find out and explain how the effect of e-service quality and e-recovery service quality on e-customer loyalty when online shopping is mediated by e Green Human Resource Management (GHRM) at hotels in Kerinci and Sungai Penuh, either directly or indirectly. direct. this research is quantitative. The sampling method used was purposive sampling with a research instrument in the form of a questionnaire distributed to 80 respondents from hotel employees. The results showed that green transformational leadership and green servant leadership had a direct effect on GHRM and green creativity. GHRM has an important role in mediating the relationship between green transformational leadership and green servant leadership on green creativity. Therefore, the concept of GHRM strengthens the exchange relationship between employees and the organization because they care, support, and appreciate their contribution, when green servant leadership, green transformational is good, hotel employees are more likely to exert their efforts and happily engage in environmentally friendly tasks. ultimately fostering eco-friendly creativity from employees.